Training-specific adaptations of H- and stretch reflexes in human soleus muscle - Gruber, M.; Taube, W.; Gollhofer, A.; Beck, S.; Amtage, F.; Schubert, M. (Journal of Motor Behavior, 2007)
The authors investigated the effect of physical exercise on reflex excitability in a controlled intervention study. Healthy participants (N = 21) performed 4 weeks of either power training (ballistic strength training) or balance training (sensorimotor training [SMT]). Both training regimens enhanced balance control and rate of force development, whereas reductions in peak-to-peak amplitudes of stretch reflexes and in the ratio of the maximum Hoffman reflex to the maximum efferent motor response (Hmax:Mmax) measured at rest were limited to SMT. The differences in reflex excitability between the training regimens indicated different underlying neural mechanisms of adaptation. The reduced reflex excitability following SMT was most likely induced by supraspinal influence. The authors discuss an overall increase in presynaptic inhibition of Ia afferent fibers as a possible mechanism.